2016
DOI: 10.1007/s00146-016-0667-2
|View full text |Cite
|
Sign up to set email alerts
|

The case of classroom robots: teachers’ deliberations on the ethical tensions

Abstract: Robots are increasingly being studied for use in education. It is expected that robots will have the potential to facilitate children's learning and function autonomously within real classrooms in the near future. Previous research has raised the importance of designing acceptable robots for different practices. In parallel, scholars have raised ethical concerns surrounding children interacting with robots. Drawing on a Responsible Research and Innovation perspective, our goal is to move away from research con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
147
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(172 citation statements)
references
References 57 publications
3
147
2
1
Order By: Relevance
“…This approach should, of course, be discussed in relation to the ethical implications it holds. For example, empathic relations with robots could potentially be understood as deceptive 17 , and present a number of implications, which in the longer term may be deemed undesirable by, e.g., teachers 73 . Notwithstanding, it has also been questioned whether robots could even reach a stage where they can be considered empathic 76,75 .…”
Section: Introductionmentioning
confidence: 99%
“…This approach should, of course, be discussed in relation to the ethical implications it holds. For example, empathic relations with robots could potentially be understood as deceptive 17 , and present a number of implications, which in the longer term may be deemed undesirable by, e.g., teachers 73 . Notwithstanding, it has also been questioned whether robots could even reach a stage where they can be considered empathic 76,75 .…”
Section: Introductionmentioning
confidence: 99%
“…These respondents from autism education settings shared many basic perceptions of robots with both the mainstream, UK-based educators in Kennedy et al (2016), including robots as having "simplistic interactions" and being "primarily seen as a scripted, reactive machine" (p. 5), and with the Canada-based special educators in Diep et al (2015), who felt that robots might "[provide] structure and repetitiveness in a consistent fashion" (p. 2). Yet, the same qualities that our participants saw as potentially so promising for meeting the needs of autistic learners were perceived as obstacles to adoption by the Kennedy et al (2016) mainstream sample (see also Serholt et al, 2017); an illustration that "educators, " "autistic children" and "schools" are not homogenous groups and will have different needs-which need to be fully understood to inform future robotics work.…”
Section: Discussionmentioning
confidence: 77%
“…Several studies have sought teachers and professionals' views to explore implementing robots within regular educational settings (Fridin and Belokopytov, 2014;Kennedy et al, 2016;Serholt et al, 2017;Cheng et al, 2018) but only a handful have done so within special education settings. Diep et al (2015) interviewed six teachers from a Canadian school for children with multiple and complex needs about their perceptions of social robots, in relation to an anticipatory governance framework (Guston, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, psychology-driven ethical appraisals such as outlined by Amanda and Noel Sharkey [45,46] do highlight issues of emotional attachment, deception of the child, and loss of human contact (see also [33]). Apropos teachers' attitudes to robots in the classroom, research reported in [47] demonstrates the exigency of taking the consideration of ethics beyond design issues and toward engagement with stakeholders' views on how robots may affect their current practices. The point made here, however, concerns biases located in one side of a schism within the discourse of social robotics [10,43,48].…”
Section: How Could Biases Of the Technological Imagination Be Avoided?mentioning
confidence: 99%